The Effect of Price, Service Quality, and Facilities on the Satisfaction of Umrah Pilgrims at PT Putra Duta Wisata, Palembang - Prameliza Alfianti; Sari Lestari Zainal Ridho; Dwi Riana (Surplus: Jurnal Ekonomi dan Bisnis, 2026)
This study is entitled "The Effect of Price, Service Quality, and Facilities on the Satisfaction of Umrah Pilgrims at PT Putra Duta Wisata in Palembang City". This study aims to determine and analyze the effect of price, service quality, and facilities on the satisfaction of Umrah pilgrims at PT Putra Duta Wisata. Pilgrim satisfaction is one of the important indicators in the success of organizing Umrah pilgrimage travel services. The research method used is a quantitative approach with data collection techniques through distributing questionnaires to 64 respondents who are Umrah pilgrims of PT Putra Duta Wisata. The data obtained were analyzed using multiple linear regression analysis with the help of SPSS 27.0 software to determine the effect of each independent variable on the dependent variable. The results of the study showed that price, service quality, and facilities simultaneously had a significant effect on pilgrim satisfaction. In part, the three variables also had a positive and significant effect, with service quality being the most dominant factor. This study provides implications for company management to continue to improve the quality of service and facilities in order to maintain and increase the satisfaction of PT Putra Duta Wisata pilgrims.